Early childhood caries prevalence and associated factors among preschoolers aged 3–5 years in Xiangyun, China: A cross-sectional study - Liu, Mingshan; Song, Qianqian; Xu, Xiaoqin; Lai, Guangyun (Frontiers in Public Health, 2022)
Purpose This study aimed to investigate the early childhood caries (ECC) prevalence among preschoolers aged 3-5 years in Xiangyun of Yunnan, China and explore the factors associated with the prevalence. Materials and methods A cross-sectional survey including 3-5-year-old children was conducted in Xiangyun County, China, between September and November 2020. According to the dental examination standard of the WHO 2013 criteria, the presence of ECC was recorded. Besides the dental examination for children, their parents completed questionnaires about caries-related factors, including demographic variables, family socioeconomic status, feeding, and oral health-related habits, parental dental knowledge, and the condition of dental service utilization. SPSS Statistics 25.0 (IBM, Chicago, IL, USA) was used for data analysis. Statistical significance was set at p < 0.05. Results The ECC prevalence among a sample of 1,280 children aged 3–5 years consisting of 665 boys and 615 girls in this study, was 74.3%, and the mean decayed-missing-filled teeth (dmft) was 4.9 ± 5.0. There were no statistically significant differences in the ECC prevalence between the sexes and among different ethnic groups. Children with different dietary and oral hygiene habits showed no significantly different prevalence of ECC. Logistic regression analysis showed that the most significantly associated factors were older age, lower family income, and worse parental perception of children's oral health status. Conclusion The ECC prevalence among 3–5-year-old preschool children in Xiangyun was higher than the average national ECC prevalence in China. This study implies that more attention should be given to children's caries prevention from early childhood; oral health education and promotion should be intensified to reduce the ECC prevalence and improve the oral health status of children in Xiangyun.